Anatomy & physiology revealed [ - Schneider, R. E. [ (Roy E.)] (McGraw-Hill Higher Education, 2007)
Esperince interactive cadaver dissection with anatomy & physiology revealed cadaver photos blended with a state-of-the art layering technique let you peel away layers of the human body to reveal structures beneath of surface. This easy-in-use program includes animation, radiologic imaging, audio pronunciations and a comprehensive quizzing tools